The Relationship Between Internal Employer Branding and Talent Retention: A Theoretical Investigation for the Development of a Conceptual Framework - Ahmed, Rizwan Raheem; Azam, Muhammad; Qureshi, Jawaid Ahmed; Hashem E, Alharthi Rami; Parmar, Vishnu; Md Salleh, Nor Zafar (Frontiers in Psychology, 2022)
The focus of this paper is to develop a comprehensive conceptual framework for the relationship between internal employer brand image and talent retention. An extensive and semi-systematic literature review identified a number of antecedents and consequences that have been empirically tested in various cutting-edge research studies conducted around the world. The existing literature is reviewed using a topical approach, and sixty-six research studies, mostly recent from various repositories were carefully chosen and reviewed based on the criteria. Such studies have been discerned and synthesized in order to establish a complete and accurate understanding of the phenomenon. Finally, a comprehensive and relatively rich conceptual framework has been proposed for future empirical explanations in various social settings via prospective research.